2018
DOI: 10.7717/peerj.5071
|View full text |Cite
|
Sign up to set email alerts
|

Methods matter: the relationship between strength and hypertrophy depends on methods of measurement and analysis

Abstract: PurposeThe relationship between changes in muscle size and strength may be affected by both measurement and statistical approaches, but their effects have not been fully considered or quantified. Therefore, the purpose of this investigation was to explore how different methods of measurement and analysis can affect inferences surrounding the relationship between hypertrophy and strength gain.MethodsData from a previous study—in which participants performed eight weeks of elbow flexor training, followed by an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 76 publications
0
28
0
Order By: Relevance
“…This may be explained, at least in part, by the methods used to assess muscle growth. Specifically, evidence indicates that MT does not show a high correlation with maximal strength (Vigotsky et al, 2018). Moreover, differences in quadriceps hypertrophy were limited to only the mid-thigh at the location of the rectus femoris.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained, at least in part, by the methods used to assess muscle growth. Specifically, evidence indicates that MT does not show a high correlation with maximal strength (Vigotsky et al, 2018). Moreover, differences in quadriceps hypertrophy were limited to only the mid-thigh at the location of the rectus femoris.…”
Section: Discussionmentioning
confidence: 99%
“…Would correlations from longer term studies on the changes in skinfold thickness and muscle strength be enough [47,48]? It is hard to imagine another scenario where correlations (between or within), in the absence of experimental evidence, are sufficient to make causal claims about the importance of one variable for another variable [40,49]. If muscle growth is a meaningful contributor for strength adaptation, then this should be demonstrated through experiments.…”
Section: Reply To Taber Et Almentioning
confidence: 99%
“…Finally, while the studies presented hitherto address the question of whether those who gain more muscle also get stronger (between-subject), it has been suggested that the question of greater interest is if an individual will get stronger as they gain more muscle (within-subject) [42]. Indeed, such analyses explain a much greater percentage of variance in strength gain than do between-subject analyses [42,43]. While this work remains in its infancy and has room for improvement, both methodologically and statistically, we believe the early results to be both intriguing and thought-provoking in helping to elucidate the strengthhypertrophy relationship.…”
Section: Training Studiesmentioning
confidence: 99%
“…Since an experiment that assesses all potential mechanisms would be nearly impossible to complete in humans, multiple lines of work may be needed to establish or refute hypertrophy as a contributory cause. That is, the question may not be able to be answered through a single experiment, but rather, many experiments combined with modeling may be needed [42].…”
Section: Reply To Loenneke Et Almentioning
confidence: 99%